Preparation method of heterostructure material applied to positive electrode of supercapacitor
Through the improved metal ion impregnation method, NiFe2O4 combined with potassium ferrate and NiFe2O4 to form a heterostructured material of NiFe2O4@Fe2O3, the problems of low energy density of the supercapacitor and insufficient material conductivity are solved, and high rate performance and long cycle stability are achieved.
Patent Information
- Application Number
- CN202411664806.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The energy density of existing supercapacitors is low, and the conductivity and cyclic stability of pseudocapacitor materials such as permanganate and ferroate are insufficient, which limits their wide application in application scenarios with high energy demand.
A modified metal ion impregnation method is adopted to combine potassium ferrate with the oxide NiFe2O4 with good conductivity to form a NiFe2O4@Fe2O3 heterostructure material, thereby improving the conductivity and electrochemical stability of the electrode material.
High-rate performance and cyclic stability are achieved. The energy density retention rate of NiFe2O4@Fe2O3 heterogeneous material at high current density is as high as 62.1%, and the specific capacitance retention rate is nearly 80% after 10,000 charge and discharge cycles, which significantly improves the stability and performance of the material.
Smart Images

Figure CN119517628A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage materials, and in particular to a method for preparing a heterostructure material used for a supercapacitor positive electrode. Background Art
[0002] Supercapacitors are energy storage devices that have attracted much attention for their excellent power density, extremely fast charge and discharge speeds, and long-term cycle stability. In the past few years, they have become a promising energy storage solution in areas such as electric vehicles, mobile devices, and auxiliary power supplies. However, compared with traditional battery technology, supercapacitors have a lower energy density, which limits their widespread application in some application scenarios with higher energy requirements.
[0003] In order to improve the energy density of supercapacitors, researchers are committed to developing and optimizing the preparation methods of new electrode materials. 4 - ) and ferrate (FeO 4 2- ) are typical pseudo-capacitor materials that have attracted attention due to their ability to store charge through rapid surface or near-surface Faradaic reactions. Although they have high theoretical specific capacity, their practical applications are limited due to their poor electronic conductivity and cycle stability.
[0004] In recent years, heterostructured electrode materials, that is, composite materials composed of two or more different materials, have become a research hotspot in the field of electrode materials because they combine the advantages of multiple materials and can achieve synergistic enhancement of performance. In particular, by using oxides with good conductivity, such as RuO 2 、Co 3 O 4 、NiFe 2 O 4 The surface deposition of active materials such as permanganate or ferrate can significantly improve the conductivity and electrochemical stability of the electrode material, thereby increasing the charge storage capacity of the electrode.
[0005] As a method for preparing electrode composite materials, metal ion impregnation is favored because of its simplicity, low cost and the ability to prepare high-performance heterogeneous structures. Through the metal ion impregnation method, the uniform and tight combination of permanganate / ferrate and the substrate material can be achieved. This method not only provides a simple way to manufacture multi-component electrode active layers, but also ensures the high stability and excellent electrochemical properties of the material.
[0006] However, to achieve industrial application, more exploration is still needed on the optimization of the final material properties by the impregnation conditions and the potential combination with other cost-effective materials. This patent should provide an improved metal ion impregnation method, which can not only solve the conductivity and stability problems of existing materials, but also make breakthroughs in achieving large-scale production and reducing manufacturing costs. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing a heterostructure material used in a supercapacitor positive electrode, so as to solve the problems raised in the above background technology.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing a heterostructure material for use in a supercapacitor positive electrode, comprising the following steps:
[0009] S1: dissolving 20 parts of potassium ferrocyanide in 160 parts of deionized water to obtain solution A, and dissolving 20 parts of potassium chloride and 26 parts of nickel chloride hexahydrate in 160 parts of deionized water to obtain solution B;
[0010] S2: Add solution B dropwise to solution A and continue stirring for 20 min after the addition is complete;
[0011] S3: The mixed solution obtained in step S2 is transferred to a hydrothermal reactor with 400 parts of polytetrafluoroethylene inner liner, and after cooling to room temperature, a powder is obtained;
[0012] S4: Weigh potassium ferrate in a mass ratio of 2:1 to the powder obtained in step S3, dissolve it in 280 parts of deionized water, and perform ultrasound;
[0013] S5: transferring the mixed solution in step S4 to a hydrothermal reactor with 400 parts of polytetrafluoroethylene inner liner;
[0014] S6: Centrifugal washing and drying to obtain NiFe 2 O 4 @Fe 2 O 3 Heterogeneous material powder.
[0015] Preferably, the stirring in step S1 is performed using a centrifuge, and the stirring rate is 110-120 r / min.
[0016] Preferably, the solution B should be added to the solution A dropwise within 5 minutes, and the dropping speed is 2 mL / min.
[0017] Preferably, the centrifugal washing in step S6 is performed at least 5 times, and the washing is performed until the solution is clear.
[0018] Preferably, the drying temperature in step S6 is 60° C. and the drying time is 12 hours.
[0019] Preferably, the ultrasound in step S4 is performed using an ultrasound device, and the ultrasound time is 30 minutes.
[0020] Preferably, the heating temperature in the reactor of step S3 is 120° C., the hydrothermal reaction is carried out for 6 hours, and after 6 hours, the temperature is raised to 180° C. and the reaction is continued for 18 hours.
[0021] Preferably, in step S5, the heating temperature in the reactor is 150° C., and the hot water reaction is performed for 5 hours.
[0022] Preferably, during the process of adding solution B dropwise to solution A in step S2, the centrifugal speed of solution A is 300 r / min.
[0023] Preferably, the cooling to room temperature in step S3 needs to be performed in a dry environment.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. A NiFe of the present invention 2 O 4 @Fe 2 O 3 The heterostructure supercapacitor electrode material has high rate performance and cycle stability. Electrochemical tests show that its specific capacitance is 971F / g at 1A / g and 603.4F / g at 30A / g. At a higher current density, its specific capacitance still has a retention rate of 62.1%, indicating that this material has good rate performance; at the same time, after 10,000 charge and discharge cycle tests at a high current density of 5A / g, its specific capacitance did not decrease significantly after 10,000 charge and discharge cycles, and the specific capacitance retention rate was nearly 80%. In summary, the material structure is relatively stable, and its specific capacitance value did not decrease significantly after multiple charge and discharge cycles at high current density.
[0026] 2. A heterogeneous structure supercapacitor electrode material prepared by the present invention has a certain specific capacitance and has relatively high rate performance and cycle stability, and has a relatively simple process flow and relatively low cost. The reaction utilizes a simple impregnation method. Through ion exchange between metal ions and permanganate / ferrate ions in aqueous solution, the reaction equilibrium is biased to the right and the reaction is easy to occur. The preparation process of some heterogeneous structures requires a very complicated process and the growth of the structure is uneven. The present invention only requires a simple one-step impregnation method, and does not require the addition of a catalyst, nor does it require complex equipment and harsh storage conditions. The raw materials used in the present invention, whether nickel ferrite or potassium ferrate, are very cheap, and the solvent deionized water used is also the most commonly used solvent. The heterogeneous material prepared by the present invention provides a new idea for the development of supercapacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is to prepare NiFe by impregnation method 2 O 4 @Fe 2 O 3 Flowchart of heterogeneous materials;
[0028] Figure 2 The NiFe 2 O 4 @Fe 2 O 3 XRD patterns of heterogeneous materials;
[0029] Figure 3 The NiFe 2 O 4 @Fe 2 O 3 Comparison of cyclic voltammetry (CV) curves of heterogeneous materials and NiFe2O4;
[0030] Figure 4 The NiFe 2 O 4 @Fe 2 O 3 Cyclic voltammetry (CV) graphs of heterogeneous materials;
[0031] Figure 5 The NiFe 2 O 4 @Fe 2 O 3 Constant current charge-discharge curves (GCD) of heterogeneous materials and NiFe2O4 at different current densities;
[0032] Figure 6 The NiFe 2 O 4@Fe 2 O 3 Constant current charge and discharge curves (GCD) of heterogeneous materials at different current densities
[0033] Figure 7 The NiFe 2 O 4 @Fe 2 O 3 Rate performance diagram of heterogeneous materials;
[0034] Figure 8 The NiFe 2 O 4 @Fe 2 O 3 Cyclic stability diagram of heterogeneous materials. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example: See Figure 1-Figure 8 The present invention provides a technical solution: a method for preparing a heterostructure material for a supercapacitor positive electrode, comprising the following steps:
[0037] S1: dissolving 20 parts of potassium ferrocyanide in 160 parts of deionized water to obtain solution A, and dissolving 20 parts of potassium chloride and 26 parts of nickel chloride hexahydrate in 160 parts of deionized water to obtain solution B;
[0038] S2: Add solution B dropwise to solution A and continue stirring for 20 min after the addition is complete;
[0039] S3: The mixed solution obtained in step S2 is transferred to a hydrothermal reactor with 400 parts of polytetrafluoroethylene inner liner, and after cooling to room temperature, a powder is obtained;
[0040] S4: Weigh potassium ferrate in a mass ratio of 2:1 to the powder obtained in step S3, dissolve it in 280 parts of deionized water, and perform ultrasound;
[0041] S5: transferring the mixed solution in step S4 to a hydrothermal reactor with 400 parts of polytetrafluoroethylene inner liner;
[0042] S6: Centrifugal washing and drying to obtain NiFe 2 O 4 @Fe 2O 3 Heterogeneous material powder;
[0043] The stirring in step S1 is performed by a centrifuge, and the stirring rate is 110-120 r / min;
[0044] Solution B should be added to solution A within 5 minutes, and the rate of addition is 2 mL / min;
[0045] Step S6: The number of centrifugal washing is at least 5 times, and the washing is performed until the solution is clear;
[0046] The drying temperature in step S6 is 60°C and the drying time is 12h;
[0047] The ultrasound in step S4 is performed using an ultrasound device, and the ultrasound time is 30 minutes;
[0048] Step S3: The temperature in the reactor is heated to 120°C for hydrothermal reaction for 6 hours, and then the temperature is raised to 180°C for further reaction for 18 hours;
[0049] In step S5, the temperature of the reactor in step S5 is 150°C, and the hot water is reacted for 5 hours;
[0050] In the process of adding solution B dropwise to solution A in step S2, the centrifugal speed of solution A is 300 r / min;
[0051] The cooling to room temperature in step S3 needs to be performed in a dry environment.
[0052] The specific implementation of this embodiment is as follows:
[0053] 0.5g potassium ferrocyanide was dissolved in 40mL deionized water to obtain solution A, 0.5g potassium chloride and 0.6527g nickel chloride hexahydrate were dissolved in 40mL deionized water to obtain solution B, solution B was added to solution A at a rate of 2mL / min, and stirring was continued for 20min after the addition was complete. The mixed solution was transferred to a hydrothermal reactor with a 100mL polytetrafluoroethylene liner, and the hydrothermal reaction was carried out at 120℃ for 6h. After 6h, the temperature was immediately raised to 180℃ and the reaction was continued for 18h. After the reaction was completed, the mixture was cooled to room temperature in a drying oven, centrifuged and washed, and dried at 60℃ for 12h to obtain a powder. Potassium ferrate with a mass ratio of 2:1 to the above-obtained powder was weighed, dissolved in 70ml deionized water, and ultrasonicated for 30min. The mixed solution was transferred to a hydrothermal reactor with a 100mL polytetrafluoroethylene liner, and the hydrothermal reaction was carried out at 150℃ for 3h, centrifuged and washed, and dried at 60℃ for 12h to obtain NiFe 2 O 4 @Fe 2 O 3 Heterogeneous material powders;
[0054] (1) Figure 3 NiFe is shown 2 O 4 @Fe 2 O 3 In the CV diagram of 5mV / s-100mV / s, it can be seen from the figure that at different scanning speeds from 5mV / s to 100mV / s, NiFe 2 O 4 @Fe 2 O 3 Both show obvious redox reversible peaks, indicating that this material can undergo redox reactions to store charge. As the scan rate increases from 5 to 100 mV / s, the anode peak moves to a higher potential, while the cathode peak moves to a lower potential. This phenomenon is mainly due to the increase in the scan rate leading to polarization. When the scan rate increases by 100 mV / s, the shape of the CV curve remains unchanged, indicating that the NiFe 2 O 4 @Fe 2 O 3 Can maintain good charge and discharge performance at a faster scan rate;
[0055] (2) Figure 4 Shown is the NiFe 2 O 4 @Fe 2 O 3 In the GCD graph at current density of 1A / g-30A / g, the voltage platform in the GCD curve shows a nonlinear curve, which corresponds to the typical battery performance. In addition, the GCD graph still has good symmetry at high current density, indicating that the NiFe 2 O 4 @Fe 2 O 3 Has excellent reversible charge and discharge capabilities;
[0056] Calculate the specific capacitance using the formula:
[0057]
[0058] Where C is the specific capacitance (F / g), I is the charge and discharge current (A), t is the discharge time (s), ΔV is the potential window (V), and m is the mass of the active material (g). The calculation results show that at a current density of 1A / g, NiFe 2 O 4 @Fe 2 O 3It has a specific capacitance of 927F / g, a specific capacitance of 971F / g at a current density of 1A / g, a specific capacitance of 941.8F / g at a current density of 3A / g, a specific capacitance of 690.9F / g at a current density of 15A / g, and a specific capacitance of 606.06F / g at a current density of 30A / g;
[0059] (3) By Figure 6 And (2) content, NiFe 2 O 4 @Fe 2 O 3 The specific capacitance at a high current density of 30 A / g is 62.1% of that at a current density of 1 A / g, which indicates that NiFe 2 O 4 @Fe 2 O 3 When used as a supercapacitor electrode material, it has good rate performance;
[0060] (4) By Figure 8 As shown, in order to verify the cycling stability of p-phenylenediamine glyoxal at high current density, we performed 10,000 charge and discharge cycles at a current density of 5 A / g. 2 O 4 @Fe 2 O 3 After 10,000 cycles, the specific capacitance loss is very small, and the specific capacitance retention rate is 79-80%, which fully demonstrates that NiFe 2 O 4 @Fe 2 O 3 The heterostructure is well-stable and its structure is not destroyed even under high current density and long cycle.
[0061] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels.
[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a heterostructure material for use in a supercapacitor positive electrode, characterized in that: The following steps are involved: S1: dissolving 20 parts of potassium ferrocyanide in 160 parts of deionized water to obtain solution A, and dissolving 20 parts of potassium chloride and 26 parts of nickel chloride hexahydrate in 160 parts of deionized water to obtain solution B; S2: Add solution B dropwise to solution A and continue stirring for 20 min after the addition is complete; S3: The mixed solution obtained in step S2 is transferred to a hydrothermal reactor with 400 parts of polytetrafluoroethylene inner liner, and after cooling to room temperature, a powder is obtained; S4: Weigh potassium ferrate in a mass ratio of 2:1 to the powder obtained in step S3, dissolve it in 280 parts of deionized water, and perform ultrasound; S5: transferring the mixed solution in step S4 to a hydrothermal reactor with 400 parts of polytetrafluoroethylene inner liner; S6: centrifugal washing and drying to obtain NiFe2O4@Fe2O3 heterogeneous material powder.
2. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The stirring in step S1 is performed using a centrifuge, and the stirring rate is 110-120 r / min.
3. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The solution B should be added to the solution A dropwise within 5 minutes, and the speed of addition is 2 mL / min.
4. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The number of centrifugal washing in step S6 is at least 5 times, and the washing is performed until the solution is clear.
5. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The drying temperature in step S6 is 60° C., and the drying time is 12 hours.
6. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The ultrasound in step S4 is performed using an ultrasound device, and the ultrasound time is 30 minutes.
7. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The heating temperature in the reactor of step S3 is 120° C., and the hydrothermal reaction is carried out for 6 hours. After 6 hours, the temperature is raised to 180° C. and the reaction is continued for 18 hours.
8. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: In step S5, the heating temperature in the reactor is 150° C., and the hot water reaction is performed for 5 hours.
9. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: In the process of adding solution B dropwise to solution A in step S2, the centrifugal speed of solution A is 300 r / min.
10. The method for preparing a heterostructure material for a supercapacitor positive electrode according to claim 1, characterized in that: The cooling to room temperature in step S3 needs to be performed in a dry environment.